Inter-examiner reliability in the clinical examination of temporomandibular disorders: influence of age - Hassel AJ, Rammelsberg P, Schmitter M. (Blackwell Synergy, 2006)
The aim of this study was to investigate the influence of the age of the subject on inter-examiner reliability of the clinical signs of temporomandibular disorder (TMD).